PEMANFAATAN BAKTERI PENAMBAT N SEBAGAI PUPUK HAYATI DAN PENGARUHNYATERHADAP SERAPAN NITROGEN TANAMAN KEDELAI PADA ALFISOL - Rungu Yoga Pamungkas; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2017)
The nutrients in alfisols contain 0,10% of nitrogen, 111,47 ppm of sulfur (P), and 484,5 ppm of potassium (K). Meanwhile, soybean requires no less than 4,29 - 5,50% of nitrogen, 0,26 - 0,50% of phosfor, and 1,71 - 2,50% of potassium. According to the N, in average, cyanobacteria contributes to 30 kg N ha-1 crop season-1. If inoculated to the rhizosphere, the bacteria can produce 337 kg N ha-1.Â Therefore, researched the use of cyanobacteria as biofertilizer and how it influences to the absorption nutrients and to the soybean growth. This reasearch use complete random design with six to treatments, dosage of biofertilizer. Including : K pot with no treatment; P1 with 14,2 ml polybag1; P2 with 29,4 ml polybag-1; P3 with 44,11 ml polybag-1; P4 with 58,81 ml polybag-1; P5 with 73,51 ml polybag-1. Its was repeated three times.Â The bacteria increased the total nitrogen in the soil up to 0,21% (P5) and the nitrogen in the plant up to 0,91 mg plant-1 (P4). The maximum height of the soybean was 119,4 cm (P4) and the maximum number of leaves was 73 leaves (P4), both in the age of 42 DAP.